Plant Community Structure and Soil Microbial Community Diversity in Zogue Plateau Wetland - Tang Muzi (Shuitu baochi tongbao)
[Objective] The long-term changes of plant community structure (Carex muliensis, Carex meyeriana, Calthascaposa, Kobresia tibetica) and soil microbial community diversity in the Zogue Plateau wetland, and their evolutionary relationships were investigated in order to provide reference for vegetation restoration and ecological environment protection in this area. [Methods] The dynamic characteristics of aboveground and underground indexes of different plant communities were observed in four consecutive years (2016—2019). [Results] ① For plant α diversity, the Shannon-Wiener diversity index, Margalef richness index, and Pielou evenness index showed a consistent change trend that followed the order of Carex meyeriana>Carex muliensis>Kobresia tibetica>Caltha scaposa. However, the Simpson dominance index showed the opposite change trend. For plant β diversity, the Cody index also showed a consistent change trend that followed the order of C. meyeriana>C. muliensis>K. tibetica>C. scaposa, while the Sorenson index changed in the opposite trend. ② The contents of soil organic carbon, total nitrogen, total phosphorus, and total potassium showed a consistent change trend that followed the order of C. meyeriana>C. muliensis>K. tibetica>C. scaposa, and gradually increased with the increasing of years. Soil microorganisms were dominated by bacteria in the Zogue Plateau wetland, accounting for about 70% of the total microbial population, followed by Actinomycetes and fungi. The numbers of bacteria, fungi, and Actinomycetes followed the order of Carex meyeriana>C. muliensis>K. tibetica>C. scaposa, and numbers gradually increased with the increasing of years. ③ Soil microbial biomass carbon, nitrogen, and phosphorus followed the order of C. meyeriana>C. muliensis>K. tibetica>C. scaposa, and values gradually increased with the increasing of years. However, no significant differences were found in microbial biomass phosphorus among different years (p>0.05). ④ Soil microbial evenness index (E), species richness index (H), and carbon source using basic richness index (S) followed the order of C. meyeriana>C. muliensis>K. tibetica>C. scaposa, and values gradually increased with the increasing of years, while the dominance index (Ds) showed the opposite change tend, with no significant difference among different years (p>0.05). ⑤ Soil microbial community diversity and plant diversity were significantly correlated with each other (p<0.05). [Conclusion] There is a strong coupling between aboveground vegetation diversity and microbial community diversity in the Zogue Plateau wetland, and this coupling do not change with year, thereby indicating a unified response to changing environments.